Digital Learning: Modeling and Simulation of Three-Phase Short Circuit Fault Currents Using the Case Method for Strengthening MBKM Policy - Rahmaniar Rahmaniar; Agus Junaidi; Adi Sastra P. Tarigan; Dicky Lesmana; M. Rizki S.; Abd. Hakim Butar-Butar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study discusses learning innovations in the field of electrical engineering for the study of short circuit analysis with real data using a computer program. Students work on projects from real data in the field. The proposed method is to design a short circuit analysis programming device based on Matlab GUI. The syntax and GUI media are validated by experts. So that the standard procedure is valid for students in working on projects in real cases. At the initial stage, small-scale trial data was conducted on 15 students as an experimental class with a GUI in learning. 15 students in another class as the control class. The test results show that the experimental class has better learning independence than the control class, which is indicated by the ability to solve real problems with better project report results. The results show that the role of the GUI in digitizing learning becomes a tool to help foster motivation and independence in electric power system analysis learning to support the MBKM policy of the Ministry of Education and Culture of the Republic of Indonesia in one aspect of the Main Performance Indicators that applies the case method in learning.